Responsible criminal policy / Crime and criminal policy - AROMAA, KAUKO (Kriminologijos studijos, 2014)
Criminal policy may be assessed in a framework that is defined by the logical basic elements of crime. These are the motivated and able offender, the victim or target, and control. It is only in certain combinations of these three elements that a crime can take place, and criminal policy addresses one or several of these elements.The objectives of criminal policy are defined being fourfold: 1) to minimise tha social costs of crime; 2) to minimise the costs of crime control; 3) to distribute these costs; and 4) to do this in a fair manner. It is such considerations that are to be accounted for if knowledge-based criminal policy is to be defined and implemented. In real-life terms, this is rarely being done comprehensively. Criminal policy is, in contrast, often simplistically understood as „fighting crime“, i.e. in terms of warfare.Today, criminal policy requires careful consideration in particular because both crimes and their environment are undergoing rapid change. This puts decision-making in a particularly demanding situation and accentuates the need for valid knowledge of the situation. Therefore, there is great need of updated research on old and new forms of crime, and such research should address all central elements of crime.The near future of criminal policy is much influenced by financial crisis. This creates high demands for a more consciously knowledge-based and better quality crime control. The near future may see both positive and negative developments, the negative ones being more likely if criminal policy is not made in a responsible and comprehensive manner. The alternative of a „positive“ criminal policy is suggested as a utopian but achievable goal.Key Words: crime, criminal policy, future